PENGARUH KREATIVITAS BELAJAR DAN MINAT BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA MAN 1 POLEWALI MANDAR - Adriani Adriani; Fauziah Hakim; Sitti Inaya Masrura (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the effect of learning creativity and interest in learning mathematics on mathematics learning outcomes for students of class XI IPA MAN 1 Polewali Mandar. This research is an ex-post facto causal research with a research sample of 72 students, namely 20 students of class XI IPA 1, 20 students of class XI IPA 2, and 20 students of class IPA 3, 12 students of class XI IPA 4 MAN 1 Polewali Mandar selected by using proportionate stratified simple random sampling. Data collection techniques used the following instruments: (1) mathematics learning interest questionnaire, (2) interest in learning mathematics questionnaire, (3) mathematics learning outcomes test. Data analysis using descriptive analysis and inferential analysis. The result of the descriptive analysis of the data showed that: (1) learning creativity was in the high category, (2) interest in learning was in the medium category, and (3) students’ mathematics learning outcomes were in the medium category. The results of hypothesis testing using simple linear regression analysis and multiple linear regression, namely: (1) learning creativity has a positive and significant effect on students mathematics learning outcomes, (2) interest in learning has a positive and significant learning outcomes, (3) learning creativity and interest in learning has a positive and significant effect on students mathematics learning outcomes.